Efficient removal of U(vi) from simulated seawater with hyperbranched polyethylenimine (HPEI) covalently modified SiO2 coated magnetic microspheres. Issue 6 (17th April 2018) - Li, Wenting; Liu, Qi; Chen, Rongrong; Yu, Jing; Zhang, Hongsen; Liu, Jingyuan; Li, Rumin; Zhang, Milin; Liu, Peili; Wang, Jun
Abstract : Hyperbranched polyethylenimine (HPEI) covalently modified SiO2 coated magnetic microspheres were prepared for the efficient U(vi ) removal from simulated seawater. Abstract : Herein, we report on magnetic microspheres with numerous imine groups on the surface, which have great potential for U(vi ) recovery in seawater. Hyperbranched polyethylenimine (HPEI) was covalently grafted onto the surface of the core–shell structured microspheres Fe3 O4 @SiO2 . The microstructure and chemical composition of Fe3 O4 @SiO2 -HPEI were comprehensively characterized. Consequently, the adsorption performance at low concentrations (3–30 μg L −1 ) under simulated seawater was investigated and the removal rate reached more than 90%. The superior performance of the Fe3 O4 @SiO2 -HPEI is attributed to electrostatic force and chemical bonding (between amine/imine groups and U(vi )). We recommend, therefore, Fe3 O4 @SiO2 -HPEI as a prospective alternative adsorbent in U(vi ) recovery from seawater.